Data from: Acute sleep loss results in tissue-specific alterations in epigenetic state and metabolic fuel utilization in humans - Jonathan Cedernaes; Christian Benedict (Uppsala University, 2018)
RNA-seq data and DNA methylation array data from 15 study participants. Biopsies were takes from adipose tissue and muscle, on two occasions: after a night of normal sleep and after a night of total sleep deprivation.
Keywords: Nucleotide sequence data; Medical and Health Sciences; Medicin och hälsovetenskap